Characterization of Ketoprofen/Methyl-β-Cyclodextrin Complexes Prepared Using Supercritical Carbon Dioxide - Mauro Banchero; Silvia Ronchetti; Luigi Manna (Journal of Chemistry)
Complexes of methyl-β-cyclodextrin and ketoprofen, a crystalline anti-inflammatory drug with poor water solubility, have been prepared for the first time in the presence of supercritical CO2 at 40°C and 20 MPa. The supercritical treatment allows these pharmaceutical formulations to be prepared without the use of any auxiliary agents or organic solvents. The treated samples were characterized through differential scanning calorimetry, X-ray diffractometry, and the Fourier transform infrared spectroscopy to exclude the presence of crystalline drug and check the formation of the complexes. The increase of the drug dissolution rate was investigated performing in vitro release tests in aqueous solutions. The results showed that the supercritical treatment can be an efficient method to obtain inclusion complexes with enhanced release kinetics. The operating methods of the release tests, that is, the “tablet method” or the “dispersed amount method,” affected both the dissolution rate and its dependence on the drug amount in the samples. On the contrary, the variation of the pH of the dissolution medium did not show any effect on the release rate of the supercritical complexes.